Ekstrak Daun Sirih Merah (Piper Crocatum) Efektif Menghambat Bakteri Staphylococcus Aureus: Uji In Vitro - Tyas, Dyah Istining; Nuraini, Indria; Hubaedah, Annah (WOMB Midwifery Journal, 2024)
Alkaloids, flavonoids, saponins, and tannins are some of the antibacterial components found in the red betel (Piper crocatum). The aim of this study was to compare the antibacterial inhibitory power of red betel leaf (Piper crocatum) extract with cefadroxil against staphylococcus aureus and determine how well the extract inhibits bacterial growth in vitro using the diffusion method. An in vitro laboratory experiment with a true experimental post-test only control group design was the design used for this research. It was found that 30% (16.3mm) and 45% (16.8mm) concentrates had a strong resistance response, while 60% (18.8mm) and 100% (22.1mm) concentrates had the inhibitory response is very strong. In the positive control group, the inhibitory power was found to be 30.6mm, which shows that the inhibition zone formed was larger than in all red betel leaf extract treatments. All treatment group data were normally distributed, according to the results of statistical analysis in homogeneity and normality tests (p>0.05). Staphylococcus aureus grows more slowly and in fewer numbers when the red betel leaf extract content is greater. To determine the level of safety and toxicity, further studies on the antibacterial properties of red betel leaf extract in vivo are needed.